Public perception of the use of television in promoting healthy water consumption - Habibu, Richifa Aminu; Joseph, Ayodele Babatunde (YAYASAN MITRA PERSADA NUSANTARA, 2023)
The Mass Media plays a crucial role in advocacy and publicity, influencing people's mindset and perceptions, thereby affecting their behavior. This study focuses on understanding the public perception of television's role in promoting healthy water consumption in Kaduna state, with the aim of managing solid incidents. Using the magic bullet theory of the press and a survey research design, 60 respondents were sampled through stratified sampling. The study revealed that television programs enlighten people about the importance of using hygienic water and increase their knowledge about water usage. It concludes that television is instrumental in achieving SDG goals by propagating the significance of healthy water consumption among Kaduna state residents. The study recommends that all media organizations in Kaduna state should implement similar programs to raise awareness about the importance of clean drinking water. Additionally, television programs should educate the public about water contamination and its effects on human health.